2009
DOI: 10.1108/02656710910928789
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure and core quality management practices: how do they affect quality?

Abstract: Purpose -This empirical study seeks to resolve the conflicting findings in the quality management (QM) literature about how different QM practices, specifically, infrastructure QM practices and core QM practices, affect quality performance. Design/methodology/approach -Based on the Socio-Technical Systems theory and research related to QM implementation and performance, the study proposes a research model of the relationship between infrastructure and core QM practices and their direct and indirect effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
168
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(189 citation statements)
references
References 58 publications
10
168
2
9
Order By: Relevance
“…A further interesting contribution concerns the way we deal with the concept of QM, which is examined from a holistic perspective and, as a consequence, the introduction of QM is evaluated according to the introduction of a whole set of different practices. Thus, in line with other studies such as those of Yong and Wilkinson (2001);Rahman (2004); Bou et al (2009);Zu (2009) or Zairi and Alsughayir (2011) we conclude that organisations take a holistic approach to introduce QM by considering hard and soft dimensions of QM. As our modified structural model shows, QM is a broad framework in which different practices coexist in order to influence labour flexibility.…”
Section: Further Advances From Previous Contributionssupporting
confidence: 66%
See 1 more Smart Citation
“…A further interesting contribution concerns the way we deal with the concept of QM, which is examined from a holistic perspective and, as a consequence, the introduction of QM is evaluated according to the introduction of a whole set of different practices. Thus, in line with other studies such as those of Yong and Wilkinson (2001);Rahman (2004); Bou et al (2009);Zu (2009) or Zairi and Alsughayir (2011) we conclude that organisations take a holistic approach to introduce QM by considering hard and soft dimensions of QM. As our modified structural model shows, QM is a broad framework in which different practices coexist in order to influence labour flexibility.…”
Section: Further Advances From Previous Contributionssupporting
confidence: 66%
“…Following Bollen (1989), by inspecting modification indices scholars can determine whether the data suggests alternative theoretical models. Taking into account the information reported by the LMTEST, and based on theoretical arguments, we re-specify the initial model by classifying the QM practices into two dimensions: social, soft or instrumental QM; and technical, hard or core QM (Yong & Wilkinson, 2001;Rahman, 2004;Lewis, Pun, & Lalla, 2006;Bou, Escrig, Roca, & Beltrán, 2009;Fotopoulos & Psomas, 2009;Gadenne & Sharma, 2009;Zu, 2009;Psychogios, 2010;Zairi & Alsughayir, 2011). In this final model QM was conceived as a latent construct that accounts for the correlation between the hard and soft dimensions (Figure 2), a correlation that captures a widespread idea in QM literature: that soft or hard QM issues cannot be managed in isolation because both dimensions are needed for successful QM implementation (Hackman & Wageman, 1995;Sun, 1999;Zu, 2009).…”
Section: Structural Model: the Relationship Between Qm And Labour Flementioning
confidence: 99%
“…In addition, design for producibility and simplification would better standardize components, make it easier to produce, and lead to higher process efficiency [12,23,73]. The positive contribution of product design was demonstrated in [30,55].…”
Section: Analytical Framework and Hypotheses Developmentmentioning
confidence: 97%
“…Regarding economic aspect, there are empirical studies investigating the linkage between quality management practices and financial performance [23,28,32,49], organizational performance [50], and business performance [24]. Some studied examined QM and antecedent of economic performance such as operational performance [12,28,38,39,[51][52][53][54], production performance [34], and quality performance [22,23,26,33,55,56]. Regarding environmental performance, some studies found the contribution of quality management system to environmental performance [4,[57][58][59][60].…”
Section: Research On Quality Management and Sustainability Performancementioning
confidence: 99%
“…Zu (2009) named some of HRM indices in Six Sigma implementation projects under the name of 'infrastructure QM', such as 'top management support', 'workforce management' and 'customer relationship' these notions have been adapted from HRM practices.…”
Section: Literature Reviewmentioning
confidence: 99%